Global Grassland Diazotrophic Communities Are Structured by Combined Abiotic, Biotic, and Spatial Distance Factors but Resilient to Fertilization - Nepel, Maximilian; Angel, Roey; Borer, Elizabeth T.; Frey, Beat; MacDougall, Andrew S.; McCulley, Rebecca L.; Risch, Anita C.; Schütz, Martin; Seabloom, Eric W.; Woebken, Dagmar (Frontiers in Microbiology, 2022)
Grassland ecosystems cover around 37% of the ice-free land surface on Earth and have critical socioeconomic importance globally. As in many terrestrial ecosystems, biological dinitrogen (N2) fixation represents an essential natural source of nitrogen (N). The ability to fix atmospheric N2 is limited to diazotrophs, a diverse guild of bacteria and archaea. To elucidate the abiotic (climatic, edaphic), biotic (vegetation), and spatial factors that govern diazotrophic community composition in global grassland soils, amplicon sequencing of the dinitrogenase reductase gene—nifH—was performed on samples from a replicated standardized nutrient (N, phosphorus (P)) addition experiment in 23 grassland sites spanning four continents. Sites harbored distinct and diverse diazotrophic communities, with most of reads assigned to diazotrophic taxa within the Alphaproteobacteria (e.g. Rhizobiales), Cyanobacteria (e.g. Nostocales), and Deltaproteobacteria (e.g. Desulforomonadales) groups. Likely because of the wide range of climatic and edaphic conditions and spatial distance among sampling sites, only a few of the taxa were present at all sites. The best model describing the variation among soil diazotrophic communities at the OTU level combined climate seasonality (temperature in the wettest quarter and precipitation in the warmest quarter) with edaphic (C:N ratio, soil texture) and vegetation factors (various perennial plant covers). Additionally, spatial variables (geographic distance) correlated with diazotrophic community variation, suggesting an interplay of environmental variables and spatial distance. The diazotrophic communities appeared to be resilient to elevated nutrient levels, as 2 to 4 years of chronic N and P additions had little effect on the community composition. However, it remains to be seen, whether changes in the community composition occur after exposure to long-term, chronic fertilization regimes.